2022
DOI: 10.1155/2022/3972150
|View full text |Cite
|
Sign up to set email alerts
|

A Lip Repositioning Technique Using Polyester Threads for Gummy Smile Treatment

Abstract: A new technique is proposed in this study to correct the gummy smile (GS) with myotomy, combining lip repositioning with the insertion of polyester threads at the surgical site to act as a physical barrier and control relapse. 11 patients were clinically assessed (30.2 ± 7.43 years old, 90.9% females and 9.10% males). All patients presented gingival display (GD) greater than 4 mm. Hypermobile upper lip (HUL), vertical maxillary excess (VME) + HUL, altered passive eruption (APE) + HUL, and VME + APE were the et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…There are several variations for LRS with the goal of relapse minimization and improvement of long-term stability by preventing reinsertion of smile muscles to their original position [ 51 ]. These variations include frenectomy, use of adjuvants (botox), muscular amputation (myotomy), muscle dissection, muscle containment with insertion of polyester sutures [ 62 ], and periosteal suturing [ 27 ]. Mendoza-Geng et al (2022) suggested that the use of periosteal suturing with LRS caused the greatest decrease in EGD, with 5.22 mm (4.23–6.21) at 6 months and 4.94 mm (3.86–6.02) at 12 months post treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several variations for LRS with the goal of relapse minimization and improvement of long-term stability by preventing reinsertion of smile muscles to their original position [ 51 ]. These variations include frenectomy, use of adjuvants (botox), muscular amputation (myotomy), muscle dissection, muscle containment with insertion of polyester sutures [ 62 ], and periosteal suturing [ 27 ]. Mendoza-Geng et al (2022) suggested that the use of periosteal suturing with LRS caused the greatest decrease in EGD, with 5.22 mm (4.23–6.21) at 6 months and 4.94 mm (3.86–6.02) at 12 months post treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Additionally, PDO threads can be combined effectively with hyaluronic acid filler for enhanced outcomes. 13 A study by Horn et al 23 introduced a novel approach to treat gummy smiles by utilizing polyester threads as a physical barrier to impede muscle reinsertion. The choice of polyester threads as the filling material was based on their favorable characteristic, including compatibility with oral tissues, ensuring integration into the surrounding environment.…”
mentioning
confidence: 99%
“…Tawfik, propuso la realización de cirugía de reposicionamiento de labios con miotomía en donde se reportó mayor reducción de 3.57 mm a diferencia de la que es sin miotomía en donde la reducción es de 2.73 mm (Tawfik et al, 2018). Zardawi et al en 2010, modificaron la técnica original realizando una incisión en la unión mucogingival y otra por dentro de la encía queratinizada a 5 mm por debajo de la primera suturando en posición coronal, a largo plazo no hay estudios que colaboren la estabilidad de esta técnica(Zardawi et al, 2020).Chacón en 2020, después de investigar y deducir que existe una recidiva bastante elevada porque no existe una zona de anclaje propone realizar una división quirúrgica de los tejidos y suturas en el periostio, después retiramos tejido conectivo con otra incisión 5 mm por encima eliminando toda la zona del periostio, esta debe ser tanto lateral como apical pudiendo mantener los músculos intactos(Chacon, 2020).Torres et al en 2020, llega a la conclusión que algunos de los pacientes que describen sonrisa gingival tiene una depresión subnasal importante que permite que el labio superior quede alojado durante la sonrisa espontánea, por lo que el injerto de PMMA rellena esta cavidad, se realiza una incisión en bisel interno seguido de un colgajo de espesor total hasta la depresión subnasal, se realiza la manipulación del polvo y líquido y se lo coloca en la región y se fotopolimeriza, para un mejor volumen y conformación se colocan fresas. El injerto se inmoviliza con tornillos, se suturan y a los 10 días se retira(Torres et al, 2020).…”
unclassified